2016
DOI: 10.1039/c6ra10351k
|View full text |Cite
|
Sign up to set email alerts
|

β-NaGdF4:Eu3+ nanocrystal markers for melanoma tumor imaging

Abstract: Europium doped nanocrystals can be optimized to be successfully used as visualization markers for i.e. melanoma tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…We assume that this phenomenon is connected with an increase in the distance between Yb 3+ and Er 3+ ions after the shell growth and the reduction in number of Yb 3+ ions coupled to Er 3+ ions due to Yb 3+ ions diffusing out from the core to the shell region. A similar effect was already reported by Voß et al [37] and also found in our group for β-NaGdF 4 :Eu 3+ core-shell samples [38]. Hence we can conclude that for the core-shell structures the excitation mechanism is changing and seems to be the same as in the case of the ions distributed homogenously in big NCs.…”
Section: (B))supporting
confidence: 90%
“…We assume that this phenomenon is connected with an increase in the distance between Yb 3+ and Er 3+ ions after the shell growth and the reduction in number of Yb 3+ ions coupled to Er 3+ ions due to Yb 3+ ions diffusing out from the core to the shell region. A similar effect was already reported by Voß et al [37] and also found in our group for β-NaGdF 4 :Eu 3+ core-shell samples [38]. Hence we can conclude that for the core-shell structures the excitation mechanism is changing and seems to be the same as in the case of the ions distributed homogenously in big NCs.…”
Section: (B))supporting
confidence: 90%
“…Development of upconverting nanocrystals (UPNCs) paved a new path to the many new practical implementations. The unique optical properties of UPNCs such as anti-Stokes, multiband emission, long-time luminescence decay, narrow emission bands, and the absence of photobleaching make them attractive materials for bioimaging. Moreover, the efficiency of the upconversion process in UPNCs is a few orders of magnitude higher compared to that in popular two-photon fluorophores. , Recently, UPNCs were used in optogenetics to locally activate biological photoreactive molecules to control neural activity. On the contrary to the colloidal semiconducting quantum dots, UPNCs do not exhibit quantum size effect and their optical properties only weakly depend on UPNC surface changes . Therefore, the nanocrystals of a size ranging from 5 to 200 nm may have the same photoluminescence peak position, with significantly different mobility in liquid media.…”
Section: Introductionmentioning
confidence: 99%